2012
DOI: 10.2739/kurumemedj.59.53
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Cortical Activation in Schizophrenia during the Card Game ^|^ldquo;Concentration^|^rdquo;

Abstract: Summary:Various functional imaging studies have demonstrated reduced lateralization of cortical activation during neurocognitive tasks in schizophrenia. -A well-known card game, "concentration", reflects working memory (WM). We compared characteristics of hemodynamic changes in the prefrontal to temporo-parietal areas of the brain during this card game between 24 outpatients with schizophrenia and 24 age-and gendermatched healthy control subjects. Using multi-channel near-infrared spectroscopy, we measured rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“… 15 , 27 Furthermore, activation at the middle frontal area reflecting the WM system has been reported in patients with SZ while concentrating (in a card game). 23 Since the TMT and concentration require constant behavioral modification according to the purpose, the importance of not only WM but also the executive function is considered to be marked. Therefore, comparison between the controls and patients in the present study suggested that patients found it more difficult to activate the left middle frontal region related to the executive function during the free-drawing task than controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 15 , 27 Furthermore, activation at the middle frontal area reflecting the WM system has been reported in patients with SZ while concentrating (in a card game). 23 Since the TMT and concentration require constant behavioral modification according to the purpose, the importance of not only WM but also the executive function is considered to be marked. Therefore, comparison between the controls and patients in the present study suggested that patients found it more difficult to activate the left middle frontal region related to the executive function during the free-drawing task than controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the copying task, the subjects began to copy a tree illustration in front of them after instruction. Based on Igimi and Fujiki et al, 18 , 23 the task period in the present study was set at 60 seconds ( Figure 1 ). For the control conditions of both tasks as the baseline, all the subjects continued to draw “○” and “×” for 60 seconds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the probe position was decided based on the association between the channel at which changes in the oxy‐Hb level were observed during a right finger movement task and the anatomical region. The right finger movement task was correlated with the left motor cortex, and the channel corresponding to BA 4 was defined as a region near ch. 3 and ch.…”
Section: Methodsmentioning
confidence: 99%
“…23,24 In addition, Shoji et al identified channel (CH) 3 as a motor field by pinching the fingers with the same probe arrangement, and it is considered that CH 6, 10, 11, and 15 on both sides exit the dorsolateral PFC and CH 14 and 19 exit the frontal pole region. 25,26 Figure 1a shows the actual mounting arrangement.…”
Section: Measurementmentioning
confidence: 99%